Association of Parental Famine Exposure With Offspring Depression and Cognition Function - Liu, Ye; Liu, Yu; Lu, Yuzhu; Li, Jiangping; He, Shulan (Frontiers in Psychiatry, 2022)
Abstract Background The effect of early exposure to famine on depression and cognition in adulthood has been shown, but the intergenerational association of famine remain to be explored. This study focused on exploring the association of parental famine exposure with depression and cognition in the offspring. Methods Based on the Chinese Family Panel Studies database, which is a longitudinal survey, we included 5,150 individuals born between 1959 and 1961 and divided them into fetal-exposed, infancy-exposed (birth year = 1957–1958), school-age-exposed (birth year = 1949–1956), adolescent-exposed (birth year = 1946–1948), and unexposed groups. We used one-way analysis of variance, multiple linear regression, and one follow-up measurement to analyze the association between parental famine exposure and offspring depression and cognitive function. Results Compared with the unexposed group, the correlations between parental famine exposure during fetal period and their cognitive function (mother: β = -1.614, 95% CI: -2.535, -0.693; p = 0.001; father: β = -2.153, 95% CI: -3.104, -1.202, p<0.001) were significant. For the offspring, there was a negative correlation between famine exposure of fathers during the fetal period and depression in their offspring (β = -0.477, 95% CI: -0.907, -0.047; p = 0.030). There was a negative correlation between maternal famine exposure during the infant and adolescent period and cognitive function in the offspring (math test: β = -0.730, 95% CI: -1.307, -0.153; p = 0.013; word test: β = -2.346, 95% CI: -4.067, -0.625; p = 0.008). Limitations Not all variables related to depression and cognition function were included in the CFPS database, and the other unknown or unmeasured confounders may explain our results.